Повышение точности моделирования среднечасовой температуры обратного теплоносителя ТЭЦ - Махотило, К.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
A model of CHP-plant return heat carrier temperature is proposed. It is based on suggested equation for equivalent outdoor temperature that takes into account effect of wind and insolation as well as developed method of polynomial description of diurnal air temperature curves. It is shown that the variation of heat carrier flow rate can be used in model as an indicator of hot tap water consumption.